Students' Perspectives on Implementing Sequential Multimedia and Traditional Approaches in Narrative Text Learning - Angga Rahmat Hidayat; Aryati Presetyarini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The purpose of this study is to investigate how students view sequential multimedia and traditional approaches while learning narrative text. 32 students were selected to participate in this study. This study uses mixed-method design, followed by student reflections, documentation and classroom observation to provide the triangulation. frequency and percentage were used to represent the quantitative data. For qualitative data, thematic analysis was used to identify the reasons for students' learning preferences. The results showed that only 28% of students considered English difficult. Only one among 32 students reported that learning narrative text was boring. 69% of students stated that they preferred multimedia learning over traditional approaches. Most of the reasons they chose multimedia learning were because they stated it was more fun and exciting. This study demonstrates that students will not feel bored when learning narrative text when teachers apply a combination of multimedia and traditional methods sequentially.